DETEKSI DAN KUANTIFIKASI LOGAM TEMBAGA (Cu) DALAM IKAN PATIN (Pangasianodon hypophthalmus) SUNGAI MUSI PALEMBANG MENGGUNAKAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - indah, indah; Astuti , Risa; Anwar , Sarah Hanifah Az-Zahra (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Copper (Cu) is a toxic heavy metal that can accumulate in aquatic organisms, including edible fish. The Patin fish (Pangasianodon hypophthalmus) is an effective bioindicator for assessing heavy metal contamination in the Musi River, Palembang. This study determined Cu concentrations in Patin fish collected from three locations: Kuto Batu, 10 Ulu, and 5 Ulu, using Atomic Absorption Spectrophotometry (AAS). Cu levels were 0.60819 mg/kg (Kuto Batu), 1.08638 mg/kg (10 Ulu), and 1.01736 mg/kg (5 Ulu), all within the maximum limits for food safety. However, these results highlight the potential for Cu exposure in the Musi River ecosystem, which may pose cumulative risks to food safety and public health if concentrations increase over time.